(untitled) (Ágora UNLaR, 2019)
Entre la gran diversidad de escrituras escénicas, modelos estéticos y valores ideológicos que caracterizan al campo teatral argentino de la década del ‘90, la adaptación de obras fundamentales de la literatura estadounidenses conforma una importante tendencia. En especial, la dramaturgia de Eugene O´Neill y la narrativa de Raymond Carver despertaron constantemente un profundo interés en dramaturgos y directores argentinos. Aludiremos a Dos personas diferentes dicen hace buen tiempo (1995) de Rafael Spregelburd, a partir de una adaptación libre de la narrativa de Raymond Carver, y a la adaptación de Un largo camino de un día hacia la noche de Eugene O Neill, dirigida por Miguel Cavia (1999). En ambos casos, los procesos de reescritura y resemantización producen la apertura de los textos a nuevos y diversos sentidos. RAYMOND CARVER AND EUGENE O’ NEILL: ADAPTATIONS AND REINTERPRETATIONS IN THE ARGENTINE SCENE Abstract Among the great diversity of scenic Scriptures, aesthetic models and ideological values that characterize the Argentine theatrical field of the 90’s, the adaptation of fundamental pieces of American literature forms an important trend. In particular, the dramaturgy of Eugène O´Neill and narrative of Raymond Carver, constantly awoke a deep interest for playwrights and Argentine directors. We allude to Two different people say makes good time (1995) of Rafael Spregelburd from a free adaptation of Raymond Carver’s narrative, and the adaptation of a Long Day’s Journay into Night, of Eugene O’Neill, directed by Miguel Cavia (1999). In both cases, the process of rewriting and resignification produce open texts to new and different senses. Key words: American drama; adaptation; staged; the 90’s.